2010
DOI: 10.3851/imp1754
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Antiretroviral Drug Resistance among HIV-1-Untreated Patients in Guinea-Conakry and in Niger

Abstract: We reported the first antiretroviral drug resistance survey studies in antiretroviral-naive patients living in Guinea-Conakry and in Niger. The prevalence of resistance was between 6% and 9% in both sites, which is higher than most of the other countries from Western Africa region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
18
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 17 publications
9
18
0
4
Order By: Relevance
“…Only Nigeria ( n  = 183) and Cameroon ( n  = 31) were represented by a high or relatively high number of sequences. Other western (Benin, Niger, and Togo) and central (Central African Republic, Chad, Equatorial Guinea, and Gabon) African countries with circulation of subtype G at significant levels (≥5% of all HIV-1 infections) [13], [14], [15], [16], [17], [67], [68], [69], [70], [71], [72] were represented by a small number of sequences ( n ≤15) that may not fully reflect the country’s subtype G diversity, or were not represented at all in our study (Fig. S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only Nigeria ( n  = 183) and Cameroon ( n  = 31) were represented by a high or relatively high number of sequences. Other western (Benin, Niger, and Togo) and central (Central African Republic, Chad, Equatorial Guinea, and Gabon) African countries with circulation of subtype G at significant levels (≥5% of all HIV-1 infections) [13], [14], [15], [16], [17], [67], [68], [69], [70], [71], [72] were represented by a small number of sequences ( n ≤15) that may not fully reflect the country’s subtype G diversity, or were not represented at all in our study (Fig. S2).…”
Section: Discussionmentioning
confidence: 99%
“…Subtype G is the second most prevalent HIV-1 clade in West Africa accounting for nearly 30% of infections in the region [4]. Its prevalence greatly varies within and between countries, comprising 30–50% of HIV-1 infections across different regions from Nigeria [5], [6], [7], [8], [9], [10], [11], [12], 5–15% in Benin, Niger and Togo [13], [14], [15], [16], [17], and ≤4% in other western African countries [14], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30]. Similarly, the occurrence of the CRF06_cpx clade ranges from 40–50% of HIV-1 infections in Burkina Faso [18], [19], [20], to 5–15% in Benin, Ghana, Mali, Niger, Nigeria, Senegal and Togo [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [21], [22], [23], [24], [28], [29], and <3% in other western African countries [14], [26], [27], [30].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data published form Niger and GuineaConakry showed that the prevalence of transmitted virus with resistance mutation was higher: 6% in Niger and 9% in Guinea Conakry. 13 In 2008, a study in Mali showed a prevalence of 2.5% and 1% for nonnucleoside reverse transcriptase inhibitor (NNRTI) and nucleoside reverse transcriptase inhibitor (NRTI) resistance mutations, respectively. 6 No protease inhibitor (PI) resistance mutation was found.…”
Section: Introductionmentioning
confidence: 99%
“…25 In GC a single recombinant BF/F was found by phylogenetic analysis of 99 protease and RT sequences from antiretroviral-naïve patients. 7 A further study in Côte d'Ivoire identified five subtype F samples with a peptide-based enzyme immunoassay, without confirmation by sequencing. 26 The cluster of subtype F strains (clade F3) identified in GC appears to be unique as it clustered separately from both F1 and F2 subtypes with a bootstrap value of 100 (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…6 Information on the distribution of HIV-1 subtypes and drug-related mutations is of particular importance, primarily as GC initiated large-scale use of antiviral drugs in 2004. 7 Additionally, this information also has implications for the global pandemic, which has seen a marked increase in non-B subtype strains in previously subtype B-restricted areas. 8,9 Clinical differences may exist with non-B subtypes, notably with subtype D which has been reported to have increased speed of disease progression [10][11][12] and higher rates of vertical transmission 13 in comparison to other subtypes with such…”
Section: Introductionmentioning
confidence: 99%